Profiles of Maladjustment and Interpersonal Risk Factors in Adolescents - Méndez, Inmaculada; Ruiz-Esteban, Cecilia; Soto, Gloria; Granados Alos, Lucía; Matás-Castillo, Mercedes (Frontiers in Psychology, 2021)
The individual's adaptation problems can lead to risky behaviors such as drug use. This study aimed to analyze the existence of different adaptation profiles (personal, school and social) in adolescents. Thus, the study aimed to analyze the existence of significant differences in interpersonal risk factors depending on the degree of adaptation. The study participants were 1201 students of Compulsory Secondary Education (M = 14.43, Sd = 1.43), 50.6% were girls. The TAMAI Test (multifactorial adaptation self-evaluation test) and the FRIDA questionnaire (Interpersonal Risk Factors for Drug Use in Adolescence) were used. A latent class analysis revealed three different types of adaptation: a) high personal, school and social maladjustment; b) moderate personal, school and social maladjustment and; c) low personal, school and social maladjustment. The results showed the existence of significant differences between the different adaptation profiles based on interpersonal risk factors. The data obtained will help school and mental health plans to prevent misbehaving or risky behaviors